Administration of low‐dose epoetin‐alpha facilitates adherence to ribavirin in triple therapy with pegylated interferon‐alpha‐2b and telaprevir. Issue 10 (7th January 2014) - Ishida, Hisashi; Sakane, Sadatsugu; Toyama, Takashi; Fukutomi, Keisuke; Kimura, Keiichi; Sugimoto, Aya; Hibino, Kenji; Tamura, Takeshi; Iwasaki, Tetsuya; Iwasaki, Ryuichiro; Hasegawa, Hiroko; Sakakibara, Yuko; et al.
<x xml:space="preserve">Abstract</x> Aim Anemia frequently develops in patients given pegylated interferon, ribavirin (RBV), telaprevir (TVR) triple therapy and restricts treatment by forcing reduction or discontinuation of RBV administration. We investigated whether erythropoietin (EPO) could alleviate RBV‐induced anemia to help maintain the RBV dose during the first 12 weeks, the triple therapy phase. Methods Twenty‐two patients with hepatitis C virus (HCV) genotype 1 were enrolled. Hemoglobin (Hb) concentration was measured every week. If Hb reduction from the baseline was 2 g/dL or more, 12 000 IU of epoetin‐α was administrated. When further reduction (≥3 g/dL) was observed, 24 000 IU of epoetin‐α was used. Inosine triphosphatase (ITPA) single nucleotide polymorphism (rs1127354) was genotyped for all patients. Results Among the 22 patients enrolled in this study, three required RBV dose reduction due to anemia, two had to discontinue or reduce TVR and RBV due to creatinine elevation. The remaining 17 patients completed the treatment during the triple therapy phase without reduction of the RBV dose or adverse events attributable to EPO. Regardless of ITPA genotype, Hb decline was well controlled by EPO administration, whereas the total EPO dose tended to be higher in the CC genotype group. The average adherence to RBV during the triple therapy phase was 97.5%. SVR was achieved in 17 patients; two patients had viral breakthrough and three patients had relapse of HCV RNA. Conclusion EPO can be a favorable alternative to reduction of RBV to facilitate the adherence of patients on TVR‐based triple therapy.